2021
DOI: 10.3389/fcimb.2021.649815
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Microenvironment in Human Papilloma Virus-Induced Cervical Lesions—Evidence for Estrogen as an Immunomodulator

Abstract: Globally, human papilloma virus (HPV) infection is a common sexually transmitted disease. However, most of the HPV infections eventually resolve aided by the body’s efficient cell-mediated immune responses. In the vast majority of the small group of patients who develop overt disease too, it is the immune response that culminates in regression of lesions. It is therefore a rarity that persistent infection by high-risk genotypes of HPV compounded by other risk factors progresses through precancer (various grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 251 publications
(337 reference statements)
0
15
0
Order By: Relevance
“…HPV-specific CD8 cytotoxic T lymphocytes (CTLs) are needed for the immune defense against cervical cancer. However, the function of CTLs may be blunted by systemic and local immunosuppressive environments associated with tumor growth (56,57). A series of clinical trials (58)(59)(60) have shown that the immune system is unable to completely eradicate the tumor despite the presence of HPV-specific T cells in HPV-associated neoplastic tissue, which suggests the possible existence of systemic immunosuppression and an immunosuppressive TME that significantly influence the efficacy of therapeutic vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…HPV-specific CD8 cytotoxic T lymphocytes (CTLs) are needed for the immune defense against cervical cancer. However, the function of CTLs may be blunted by systemic and local immunosuppressive environments associated with tumor growth (56,57). A series of clinical trials (58)(59)(60) have shown that the immune system is unable to completely eradicate the tumor despite the presence of HPV-specific T cells in HPV-associated neoplastic tissue, which suggests the possible existence of systemic immunosuppression and an immunosuppressive TME that significantly influence the efficacy of therapeutic vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…However, excessive intake of Estrogen will result in the side effect such as vomiting, nausea and thrombosis [53]. Acetaminophen is one of the most popular analgesic and antipyretic agents, which showed an exceptional performance in increasing TACR3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…There has been significant research interest in the TME in CIN and ICC, in which multiple regulatory cells including TAMs, Tregs as well as MDSCs may play a deleterious role and help explain why some patients do not mount an immune response to the virus ( 116 ). The TME in ICC is enriched with cells expressing TGF-β and IL10 with lower expression of IL2 compared to cervicitis and CIN ( 117 ).…”
Section: Oncogenic Virusesmentioning
confidence: 99%